Manajemen Rantai Pasok Produksi Rak Piring Aluminium di Depok (Studi Kasus pada PD. Sumber Jaya Aluminium) - Lingga Yuliana (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2020)
The purpose of this research is to find out the product flow, financial flow and information flow in the management of the supply chain plate rack based on the existing supply chain so that the company can produce effectively and efficiently. The research method used is a qualitative method using a survey method that is to explain, describe and interpret a phenomenon that occurs in an object and qualitative data with the support of quantitative data. The results showed the company combining assembly material team, glass assembly team and final completion teams could accelerate production and limit cooperation with independent marketing to summarize the supply chain and prevent company losses.